PERAN KOMUNIKASI PEMERINTAH ACEH TIMUR MEMPERKENALKAN DESTINASI WISATA HALAL - Samsuar; Mukhlis, Muhammad; Maulana, Sirajul (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This article researches the East Aceh regency government's effort to give the concept and persuade society around tourism destination places related to the halal tourism concept raised by the government. This research uses a constructive paradigm and also a qualitative approach. Maximum variation technique is used in collecting data, consideration of large area and diversity of people to be involved; all of these are the key factor in this case. Data collection is sliced using the Diffusion Theory cutter by Gabriel Tarde. The result of this research shows that many communication available ways are used in making an effort by the East Aceh government, including by making an interpersonal approach with the informal leader and leading religious figures give impact toward implementing halal tourism in East Aceh regency.